Effects of increasing dietary rye levels on physicochemical characteristics of digesta and its impact on stomach emptying as well as the formation of 'doughballs' in stomachs of young pigs. (7th July 2021) - Wilke, Volker; Grone, Richard; von Felde, Andreas; Abd El‐Wahab, Amr; Wolf, Petra; Kamphues, Josef
Abstract: Despite quite similar contents of starch and crude fibre of wheat and rye, the unique non‐starch‐polysaccharide fraction of rye (e.g. high levels of arabinoxylans and fructans) might have an impact on physicochemical properties of the digesta in pigs. Forty pigs (age: 46.8 ± 5.28 days; bodyweight: 16.1 ± 4.13 kg) were divided into four treatment groups. During four weeks, the pigs received diets consisting of wheat and/or rye, barley, soy, potato protein and a mineral supplement. The sum of wheat and rye was 69% in all diets, whereby the compound feed of each group was characterized by a different ratio (%) of wheat/rye (69/0; 46/23; 23/46; 0/69, respectively). In the stomach, 'doughballs' occurred more frequently with increasing dietary rye levels (9/10; 69% rye). With higher DM content and extract‐viscosity of gastric digesta, the stomach emptying tended to be retarded in rye groups. Compared to the control group (69% wheat), maximum dietary rye levels (69%) resulted in significantly higher concentrations of lactic acid in digesta of the stomach and small intestine. With increasing lactic acid concentrations, the pH tended to be lower in small intestinal digesta. With an intensified formation of lactic acid, effects against Gram‐negative bacteria, for example Salmonella, can be expected. Moreover, because of higher viscosity and the retarded stomach emptying, there could be advantages of including rye in compound feeds when a longer lasting satiety is intended, for example when feeding pregnant sows (regularly fed restrictively).